(untitled) (Studia Prawnicze / The Legal Studies, 1992)
W sferze stosunków między Rzecznikiem Praw Obywatelskich a administracją publiczną doniosłe znaczenie ma wpływ ombudsmana na kształtowanie podstaw prawnych jej organizacji i funkcjonowania. Autorzy artykułu zwracają uwagę na trudności: przesadne upolitycznienie administracji wszystkich szczebli, brak mechanizmów samokorekcyjnych w administracji oraz obawy administracji w związku z zmianą sytuacji. In the sphere of relations between the Ombudsman and the public administration, the Ombudsman’s influence in shaping the legal basis for its organisation and functioning is of momentous importance. The authors of the article highlight the difficulties: the excessive politicisation of the administration at all levels, the lack of self-correction mechanisms in the administration and the administration’s fear of change.